View of Intellectual Disabilities in Postwar Education for Intellectual Disabilities and Research on the relationship with subject education - KASAI, Kazuma (Journal of Kyosei Studies, 2023)
In this study, the views of intellectual disabilities that have supported life-centerededucation in post-war education for intellectual disabilities, and also some discussionson life-centered education and subject education, through investigating three thinkers,Yasumasa Miki, Susumu Koide, and Tsunehiko Nagoya. The purpose of thisinvestigation is to clarify the significance of life-centered education in today'sintellectual disability education. Yasumasa Miki (1911-1984), based on the limitationsof the abilities of people with intellectual disabilities, advocated life-centered educationrather than subject-based education. Susumu Koide (1933-2014), regarded intellectualdisabilities as individuality and advocated a life-centered education that allows themto demonstrate their individuality, but stated that the relationship with subjects wasundifferentiated. Nagoya (1966-) is taking an inclusive view of intellectual disabilityand developed a theory that seeks differentiation and coexistence with subjecteducation based on life-centered education. Today's education for intellectualdisabilities emphasizes subject education, but from the life-centered education inNagoya, which can be said to be the ultimate goal, it is possible to confirm that subjecteducation should be based on life-centered education.